2020
DOI: 10.29333/pr/8485
|View full text |Cite
|
Sign up to set email alerts
|

College Student Transition to Synchronous Virtual Classes during the COVID-19 Pandemic in Northeastern United States

Abstract: This study examined undergraduate college students' perceptions, general preferences, emotional responses, and comment themes with the transition to a virtual learning classroom during the COVID-19 pandemic from a college in the northeast United States. A total of 148 students (44 males, 104 females) completed an 18-item transition to virtual classes survey. Students indicated that their professors utilized the Learning Management System effectively with virtual coursework, and that their professors adapted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
2
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 18 publications
2
63
2
12
Order By: Relevance
“…Although the stress and disruption related to the pandemic likely contributed to students' pleas for leniency, instructors should consider that pleas for leniency may also be a result of increases in difficulty level and course workload that may be occurring intentionally or unintentionally. Consistent with our findings, a survey of 148 undergraduates found nearly one-third reported one or more of their instructors had increased the workload in Spring 2020 [26]. Some practices may have created more work for students than instructors realize.…”
Section: Plos Onesupporting
confidence: 86%
“…Although the stress and disruption related to the pandemic likely contributed to students' pleas for leniency, instructors should consider that pleas for leniency may also be a result of increases in difficulty level and course workload that may be occurring intentionally or unintentionally. Consistent with our findings, a survey of 148 undergraduates found nearly one-third reported one or more of their instructors had increased the workload in Spring 2020 [26]. Some practices may have created more work for students than instructors realize.…”
Section: Plos Onesupporting
confidence: 86%
“…Indeed, an interview study with engineering students found that faculty members communicating care and increasing flexibility was a key element for supporting students [71]. In another study, students indicated the need for constant communication from instructors during remote learning [78]. Thus, developing stronger communication with students and improving "instructor social presence" in online courses, i.e., the sense that the instructor is connected and available for interactions is critical [79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…It changes the way of life in various sectors (Dube, 2020), including education (Rachmawati et al, 2020). This pandemic has a financial impact on educational institutions worldwide (Murphy, Eduljee, & Croteau, 2020). Educational institutions worldwide have been closed during this pandemic due to its massive impacts on the education system, and it affects more than 60% of students (Alqahtani & Rajkhan, 2020;Mukhtar, Javed, Arooj, & Sethi, 2020).…”
Section: Introductionmentioning
confidence: 99%